Transosteal radial free flap in palate reconstruction - Luis Nieto; Oscar De León; Rolf Smit; Zamir Paéz; Camilo Cháves (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2022)
The reconstruction of the palate has been a challenge for the reconstructive surgeon, due to the multiple complications that arise, such as infection, dehiscence, and fall of the flap used. We present the description of a new radial free flap fixation technique, commonly used for this type of reconstruction. This transosteal fixation technique prevents dehiscence and flap descent in all cases performed, by combining two widely used procedures, the radial free flap, and the Lefort I osteotomy, with excellent results.